Progress in medicinal chemistry. - Lawton, G.; Witty, D. R. (Elsevier, 2014)
Progress in Medicinal Chemistry provides a review of eclectic developments in medicinal chemistry. This volume continues in the serial's tradition of providing an insight into the skills required of the modern medicinal chemist; in particular, the use of an appropriate selection of the wide range of tools now available to solve key scientific problems, including g-secretase modulators, P2X7 antagonists as therapeutic agents for CNS disorders, N-type calcium channel modulators for the treatment of pain, and more. One of the most respected sources of current medicinal chemistry information. Useful to a broad cross-section of professionals, including chemists, biologists, doctors, and pharmacists.